Pengaruh Proporsi dan Ketebalan Sampah Kantung Plastik sebagai Pakan terhadap Survivorship dan Pertumbuhan Larva Tenebrio molitor L. (Coleoptera: Tenebrionidae) sebagai Plastik Degradator dan Pemanfaatannya sebagai Buku Ilmiah Populer - Deka Meilia Runtika (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jember, 2024)
Based on data from the Ministry of Environment and Forestry's National Waste Management Information System (SIPSN), in 2022 Indonesia produced 36 million tons of waste with a percentage of plastic waste of 18.1%. Some ways to deal with plastic bag waste are reducing the use of plastic bags, recycling plastic, using biodegradable plastic bags that are easier to degrade, or using plastic biodegraders. Biodegradators are organisms that can biodegrade. One of them is Tenebrio molitor L. This study aims to determine the effect of the proportion and thickness of plastic bag waste as feed on survivorship, growth, and degradation rate by Tenebrio molitor L. larvae. The design of this study is an experimental study with 6 treatments, 1 control and three replications. The treatments were differentiated based on the percentage of plastic, namely 30%a, 45%a, 60%a, 30%b, 45%b, and 60%b. Letter a is plastic with a thickness of 0.01mm while letter b is plastic with a thickness of 0.015 mm. The results of this study indicate that the effect of the proportion and thickness of plastic waste has a significant effect on survivorship with a significance value of 0.0009, length growth with a significance value of 0.034, biomass growth with a significance value of 0.0000, degradation rate with a significance value of 0.0000. The proportion of feed containing 60% konsentrat will give lower results compared to feed containing 30% plastic.
Reuploud file repositori 8 Apr 2026_Firli_tata
Keywords: Tenebrio molitor L; Plastic waste; Biodegradation